The Value of Formal Host-Country Education for the Labour Market Position of Refugees: Evidence from Austria - Lars Ludolph (Center for Economic Studies and ifo Institute (CESifo), 2021)
Refugees hosted across the developed world often work in low-quality jobs, regardless of education previously attained in their country of origin. In this paper, I analyse the long-term value of formal host-country education for refugees using the example of forcefully displaced Bosnians who arrived in Austria during the 1992-1995 Bosnian war. Deploying 22 years of Austrian microcensus data, I exploit the age at the time of forced migration as an instrument for the probability of receiving host-country instead of origin country education to recover local average treatment effects of education attained in Austria vis-à-vis Bosnia on labour market outcomes for refugees aged around schooling thresholds. These estimates show that attaining a formal degree in the host-country significantly reduces the probability of work below educational attainment and low-skill employment over the entire observation period. Income differences between Austrian and Bosnian degree holders are visible after more than two decades of stay in Austria. The discount on Bosnian education declines over time for men but not for women, suggesting that host-country degrees are particularly important to groups that faced cultural barriers to quality employment in their country of origin.
Keywords: 330; refugees; labour market integration; education